Analisis Kebutuhan Media Bimbingan Karier Kesiapan Kerja Di Era Digital Bagi Siswa SMK - Yolanda, Kiky Amelia; Buchori, Sahril; Saman, Abdul (Guidance : Jurnal Bimbingan dan Konseling, 2024)
Vocational High School (SMK) is a level of education that aims to prepare students to enter the world of work. However, data provided by Central Bureau of Statistics shows that SMK graduates are ranked first in the open unemployment rate in 2021 and 2022. This study aims to determine students’ needs for work readiness career guidance media, especially in the digital area. The research subjects were counseling teacher and grade XI students at SMKN 3 Makassar city. The type of research is the first step of the research and development (R&D) model of Borg and Gall. The research instruments used were interviews and questionnaires. The data analysis techniques used are descriptive data analysis and quantitative data analysis. The results showed that most students will look for work after graduation from SMK but there is no career guidance media about job readiness at school. The media needed is a digital based career guidance media with an attractive design